(3GdeTJbGJ GdeGdjI (B:s (3YbhO GdeSJbHdjGJ ,GdNjGQGJ, GdeHGOdGJ (B/s - (3GdQHjYj, MGce eMSfs; (3GdaJdGhj, ejKGb gGJa s; (3LhGf, MjOQ NVjQ s ((3YeGf(B: s (3OGQ GdjGRhQj(B, s, 2011)
1)(3GdeTJbGJ(B: (3eaghe GdYbhO GdeSJbHdjI h WHjYJgG , GdJMhW , GdGSYGQ GdMGVQI h GdeSJbHdjI h feGPL GdJSYjQ , (B2) (3GdeTJbGJ GdeGdjI `` YbhO GdNjGQGJ(B: (3YbhO GdNjGQGJ h CfhGYgG , GdeNGWQI h GdJMhW , GdeTJbGJ GdeGdjI `` YbhO GdeHGOdGJ (B: (3GdeVJbGJ GdeGdjI , YbhO GdeHGOdGJ , GdeNGWQI h GdJMhW (B.s
(3eQGLY U(B.481s
Keywords: (3GdYbhOs; (3GdeGdjIs